Artificial Multisensory Neurons with Fused Haptic and Temperature Perception for Multimodal In‐Sensor Computing. (18th August 2022) - Duan, Qingxi; Zhang, Teng; Liu, Chang; Yuan, Rui; Li, Ge; Jun Tiw, Pek; Yang, Ke; Ge, Chen; Yang, Yuchao; Huang, Ru
Abstract : Artificial Multisensory Neurons A bio‐inspired haptic‐temperature fusion neuron based on VO2 memristor is demonstrated, showing combined sensitivity to hybrid mechanical and thermal signals. Such neuron enables multimodal in‐sensor computing and suggests a promising approach towards e‐skin, neuro‐robotics and human‐machine interaction. More information can be found in article number 2200039 by Yuchao Yang and co‐workers.